Co-designing for common values: creating hybrid spaces to nurture autonomous cooperation. Issue 3 (3rd July 2019) - Bassetti, Chiara; Sciannamblo, Mariacristina; Lyle, Peter; Teli, Maurizio; De Paoli, Stefano; De Angeli, Antonella
ABSTRACT: The paper concerns the development of digitally-mediated technologies that value social cooperation as a common good rather than as a source of revenue and accumulation. The paper discusses the activities that shaped a European participatory design project which aims to develop a digital space that promotes and facilitates the 'Commonfare', a complementary approach to social welfare. The paper provides and discusses concrete examples of design artifacts to address a key question about the role of co- and participatory design in developing hybrid spaces that nurture sharing and autonomous cooperation: how can co-design practices promote alternatives to the commodification of digitally-mediated cooperation? The paper argues for a need to focus on relational, social, political and ethical values, and highlights the potential power of co- and participatory design processes to achieve this. In summary, the paper proposes that only by re-asserting the centrality of shared values and capacities, rather than individual needs or problems, co-design can reposition itself thereby encouraging autonomous cooperation.